2012
DOI: 10.1055/s-0032-1325404
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver Variability and Diagnostic Performance in US Assessment of Thyroid Nodule According to Size

Abstract: Interobserver agreements were relatively good (k = 0.637) in final US assessment regardless of nodule size in experienced radiologists. High false-positive rate was observed in US assessment in nodules less than 5 mm in maximum diameter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 9 publications
2
27
0
1
Order By: Relevance
“…The authors concluded that US surveillance may be appropriate for pediatric nodules stratified to less than high suspicion groups. US is also appealing with low intraobserver variability in performance [35]. It may be also possible to integrate an US stratification scheme with an adapted version of the TIRADS system as the TIRADS system has been well correlated with FNA results in adults [36].…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that US surveillance may be appropriate for pediatric nodules stratified to less than high suspicion groups. US is also appealing with low intraobserver variability in performance [35]. It may be also possible to integrate an US stratification scheme with an adapted version of the TIRADS system as the TIRADS system has been well correlated with FNA results in adults [36].…”
Section: Discussionmentioning
confidence: 99%
“…We found the poorest interobserver agreement when evaluating for the shape and margin of thyroid nodules, with ICC values of 0.36 and 0.19, respectively. Park et al examined the interobserver variability among 3 radiologists for 400 thyroid nodules and found that composition had the highest agreement, with a kappa value of 0.818, and margins and shape demonstrated the lowest agreement, with kappa values of 0.420 and 0.330, respectively, indicating fair agreement. Similarly, another study reported moderate agreement with regard to shape, echogenicity, calcification, and diagnostic categories (kappa = 0.42, 0.57, 0.55, and 0.55, respectively), and fair agreement for margin, echotexture, and capsule invasion (kappa = 0.34, 0.26, and 0.32, respectively) …”
Section: Discussionmentioning
confidence: 99%
“…Fifth, molecular markers such as BRAF V600E or RAS mutations are known to be helpful in the differential diagnosis of AUS/FLUS lesions, but were not used in our study. Lastly, 16 radiologists were involved in US examinations and image analysis, and interobserver variability among radiologists may have existed . Similarly, 5 cytopathologists were involved in cytological interpretation and the initial diagnosis of AUS/FLUS.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, 16 radiologists were involved in US examinations and image analysis, and interobserver variability among radiologists may have existed. [38][39][40] Similarly, 5 cytopathologists were involved in cytological interpretation and the initial diagnosis of AUS/FLUS. Although the Bethesda System provides standardized diagnostic terminology for thyroid cytopathology, morphological interpretation still remains subjective and interpretation of results has been known to vary significantly among readers, especially in nodules of indeterminate categories, 12,41,42 which may have affected our results.…”
Section: Discussionmentioning
confidence: 99%